Os estrangeirismos e os esportes eletrônicos: uma análise do jogo League of Legends - Cougo, Caroline Julie da Rosa (Universidade do Vale do Rio dos Sinos, 2018)
The present work has as an objective to classify the loanwords of the game League of Legends. In order to do so, this study is based on some theories, which are lexicology (CARVALHO, 1989), sociolinguistics (LABOV, 1983), emotions in language (ALTARRIBA, 2006) and use of linguistic codes (BAKER; JONES, 1998). By being inspired to these lexicologic study, the foreign terms were classified as adaptação, decalque and incorporação. Through sociolinguistics the language change and variation were explained. The use of certain words in specific moments was analysed through theories that relate emotions to the language used in that moment. The code alternance. i.e, the use of words of a second language in the middle of a discourse, was theorically justified according to the study of code-mixing and code-switching. By means doing this analysis, some transcriptions of the Campeonato Brasileiro de LOL (CBLOL) from the years of 2015 and 2018 were made. These transcriptions were the primary five minutes, the first blood and the last five minutes. As a result, an increase of decalque on narration is noticed - which demonstrates an attempt of reduction of foreign terms in official narratives. This phenomenon can be explained by diverse hypothesis - one of them being the will of narrators of making the language, somehow, more understandable for the people that are new on the game. However, as can be seen during this work, the language, as sociolinguistics would defend, is naturally free, even if people want to control it; and that is the reason why, in important and thrilling moments, the narrators do not use translation (decalque), but the original terms (incorporação), and correcting themselves afterwards. This monography, then, analyzes not only the game’s narration, but also the use of language in our society and what it implies.
Keywords: Sociolinguística; Lexicologia; League of legends; Código Linguístico; Emoção; Linguística; Sociolinguistics; Lexicology.; Linguistic code; Linguistic; Emotion